Códigos Perfeitos Na Métrica De Lee E A Conjectura De Golomb-Welch - Morais, George Absalao Pandino De [UNIFESP] (2017)
The Aim Of This Work Is The Study Of The Golomb-Welch Conjecture And The Relations Between Perfect Codes In The Lee Metric In Zn And Znq , Q 2 N, Q 2, And Tilings In Rn. In This Study, We Stress Two Articles: \Perfect Codes In The Lee Metric And The Packing Of Polyominoes", Written By Solomon W. Golomb E Lloyd R. Welch, Which Presents The Conjecture And Some Facts About Tilings Of Zn By Lee Spheres And \A New Approach Towards The Golomb-Welch Conjecture", Written By Peter Horak E Otokar Grosek, Which Gives A Soloution For Some Cases Of The Conjecture Introducing A New Algebraic Invariant Related To Abelian Groups.